Purinergic receptor P2RY12-dependent microglial closure of the injured blood–brain barrier - Lou, Nanhong (Proc Natl Acad Sci U S A, 2016)
Microglia are integral functional elements of the central nervous system, but the contribution of these cells to the structural integrity of the neurovascular unit has not hitherto been assessed. We show here that following blood–brain barrier (BBB) breakdown, P2RY12 (purinergic receptor P2Y, G-protein coupled, 12)-mediated chemotaxis of microglia processes is required for the rapid closure of the BBB. Mice treated with the P2RY12 inhibitor clopidogrel, as well as those in which P2RY12 was genetically ablated, exhibited significantly diminished movement of juxtavascular microglial processes and failed to close laser-induced openings of the BBB. Thus, microglial cells play a previously unrecognized protective role in the maintenance of BBB integrity following cerebrovascular damage. Because clopidogrel antagonizes the platelet P2Y12 receptor, it is widely prescribed for patients with coronary artery and cerebrovascular disease. As such, these observations suggest the need for caution in the postincident continuation of P2RY12-targeted platelet inhibition.